Pharmaceutical counseling: strategies for improvine the proficiency level of medication in patients with acute coronary syndrome - Núñez Araoz, Manuel Elías (2007)
In this investigation we compared two groups of patients with Acute Coronary Syndrom as diagnosys to measurement the level of knowledge about medications: action, possible secondary effects, way and frequency of administration. In order to do it we use the Guide of Pharmacist Counseling with its respective Test and Formats which had been elaborated by our self, the investigators, and they were validated by expert judges. For the control group hada population of 33 patients while the group of study were 32 patients, from all of them, by the statistical tests of T2 of Hotelling and its corresponding one F of Snedecor; we obtained that the group of study with the Counseling Pharmacist presents a significant difference with regard to level of knowledge about medicines in contrast to the control group in 50 days as maximum time.